Avaliação longitudinal da coagulação e fibrinólise em gestantes portadoras de fatores de risco para pré-eclâmpsia - Flavia Campos Lucena (2015)
Preeclampsia (PE) is characterized by systolic blood pressure 140mmHg or diastolic 90mmHg on at least two occasions (the interval between measurements should not be less than 6 hours) and proteinuria (protein excretion 0,3g in 24 hours urine or 30mg/dL, so the qualitative method 1+ in isolated samples) in normotensive pregnant women, after the twentieth week of pregnancy. The pressure in the absence of proteinuria is characterized as PE is associated with thrombocytopenia, renal failure, abnormal liver, pulmonary edema, or cerebral or visual symptoms. The objective of this study was to evaluate longitudinally markers of coagulation and fibrinolysis in pregnant women with risk factors for PE, who developed the disease or not. It were evaluated 23 samples from 11 pregnant women who developed PE and 55 samples of 17 who did not develop the disease in gestational periods 12-19, 20-29, 30-34 and 35-40 weeks. Plasma levels of D-Di, and PAI-1 were determined by ELISA (Sekisui Diagnostics). There was no significant difference in plasma levels of D-Di and PAI-1 in pregnant women who developed PE compared with those who did not develop the disease in four gestational periods evaluated. However, a significant increase in D-Di levels in pregnant that developed PE or not has been obtained by comparing the 12-19x30-34 gestational periods (P=0.045 and P=0.001), 12-19x35-40 (P<0.001 and P=0.000), 20-29x30-34 (P=0.048 and P=0.003) and 20-29x35-40 weeks (P=0.030 and P=0.001), respectively. It was also obtained a significant increase in PAI-1 levels in pregnant women who developed PE, comparing the gestational periods 35-40x12-19 (P=0.001), 35-40x2029 (P<0.001) and 35-40x30-34 weeks (P<0.001) and in women who did not develop the disease in 12-19x20-29 periods (P=0.004), 12-19x30-34 (P<0.001), 12-19x35-40 (P=0.001), 20-29x35-40 (P=0.009) and 30-34x35-40 weeks (P=0.002). The data support the conclusion that there was a trend of increased plasma levels of D-Di and PAI-1 in pregnant women who developed and who did not develop PE, during pregnancy, and this increase was more evident in those who developed the disease. These data suggest that plasma markers D-Di and PAI-1 are promising candidates to integrate a diagnostic algorithm for PE, to be applied after a clinical score and associated with imaging tests. The main merit of this study is to encourage new projects, carefully designed and surrounded by measures to ensure that there is no loss of participants over the same in order to account for a number of pregnant women and blood samples in each gestational period sufficient to allow, safely, determining the cut-off D-Di, and PAI-1 for the early diagnosis of the disease. The determination of D-Di would undoubtedly be of great value for PE diagnosis, knowing that this test is now available in clinical laboratories.